2011
DOI: 10.1074/jbc.m110.196493
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Protein Phosphatase 1 Inhibitor, cdNIPP1, Increases CDK9 Threonine 186 Phosphorylation and Inhibits HIV-1 Transcription

Abstract: Cyclin-dependent kinase-9 (CDK9) 3 /cyclin T1 is a protein kinase that phosphorylates the C-terminal domain of the largest subunit of RNA polymerase II during transcription elongation (1). CDK9/cyclin T1 is part of positive transcription elongation complex (P-TEFb) and present in the cells within large and small complexes. The large complex contains 7SK RNA (2, 3) and the hexamethylene bisacetamide-induced protein (HEXIM1) (4, 5). The activity of CDK9 in the large complex is inhibited by the interaction with 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 41 publications
5
58
0
Order By: Relevance
“…Second, we recently demonstrated that high doses of 1E7-03 administered to mice by injections do not result in a toxic effect (25). Third, a stable expression of PP1-sequestering cdNIPP1, although inhibitory for HIV-1, did not compromise cell growth (10). Fourth, viable cell lines stably expressing cdNIPP1 (10) and transgenic mice in which genetic PP1 inhibition through induced expression of inhibitor-1 (I-1) resulted in ϳ70% reduction of the PP1 activity (46) were developed.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Second, we recently demonstrated that high doses of 1E7-03 administered to mice by injections do not result in a toxic effect (25). Third, a stable expression of PP1-sequestering cdNIPP1, although inhibitory for HIV-1, did not compromise cell growth (10). Fourth, viable cell lines stably expressing cdNIPP1 (10) and transgenic mice in which genetic PP1 inhibition through induced expression of inhibitor-1 (I-1) resulted in ϳ70% reduction of the PP1 activity (46) were developed.…”
Section: Discussionmentioning
confidence: 96%
“…We showed that short, 2-hlong, treatment with 100 nM okadaic acid induced VP30 phosphorylation, which has not been noted before. Moreover, we used a specific PP1 inhibitor, cdNIPP1, which we previously demonstrated to be non-toxic when stably expressed in 293T cells (10), to analyze the role of PP1 in VP30 phosphorylation. Expression of cdNIPP1 increased phosphorylation of VP30, suggesting that it is controlled by PP1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the interaction of Tat with protein phosphatase PP1 56 , which contributes to stress-induced 7SK snRNP disruption through dephosphorylating Thr186 at the CDK9 T-loop 56 , could conceivably lend a helping hand to Tat in the extraction process. In agreement with this notion, PP1 has been shown to play a positive role in Tat transactivation and HIV replication 57 .…”
Section: Tat Extracts P-tefb From 7sk Snrnpmentioning
confidence: 66%